DINAMIKA IMPLEMENTASI SYARIAT ISLAM DI ACEH DALAM PERSPEKTIF SOSIO-LEGAL KONTEMPORER - Jumaini Jumaini; Andi Abdul Hamzah; Darussalam Syamsuddin (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
Islamic Sharia is a religious law that regulates the rules of human life based on the teachings of the Prophet Muhammad (SAW). and based on Al-Qur’an. This study aims to analyze the dynamics of the implementation of Islamic law (Sharia) in Aceh from a contemporary socio-legal perspective. A qualitative descriptive approach was employed, using primary data collected through questionnaires and in-depth interviews, supported by secondary data from legal documents and academic literature. The data were analyzed using thematic analysis and an interactive model of data reduction, data display, and conclusion drawing. The finding reveal that the implementation of Sharia in Aceh is a complex and multidimensional phenomenon influenced not only by legal norms but also by social, cultural, and political factors. The level of public understanding of sharia varies significantly, with many individuals demontrating only a formal or superficial understanding rather than a substantive one. In Practice, sharia implementation tends to be more symbolic, particularly in visible aspects such as dress codes and ritual observances, while its ethical and social values are not fully internalized. Furthermore, the relationship between Islamic law and national law reflects a pattern of legal pluralism, where different legal systems coexist and interact, sometimes harmoniously and at other times conflictually.